A Comprehensive Review on Anti-Cancer Properties of Amaranthus viridis - Kumar, Arun; Katiyar, Arpit; Gautam, Vijay; Singh, Rashmi; Dubey, Anubhav (Journal for Research in Applied Sciences and Biotechnology, 2022)
Amaranthus Viridis L. belongs to the Family (Amaranthaceae) commonly known as “Chowlai” which a common name. A. Viridis contains several compounds like Quercetin, Kaempferol, Hydroxycinnamic acids (HCs) (coumaric acid, ferulic acid, sinapic acid, caffeic acid, chlorogenic acid, rosmarinic acid), Syringic acid (SA), Rutin, Vitexin, Vanillic acid, etc . In search of new activities and chemical entities, phytochemical screening of the extract from leaves of A. Viridis L. indicates the presence of biologically active constituents saponins, tannins, phenols, flavonoids, alkaloids, cardiac glycoside, steroids, and triterpenoids. Quercetin is the aglycone form of several other flavonoid glycosides, Kaempferol (3,4′,5,7- tetrahydroxyflavone) is a natural flavonol, a type of flavonoid, Syringic acid (SA) is a phenolic compound of natural origin. Syringic acid (SA) is a phenolic compound which obtained from natural origin. SA is an excellent compound to be used as a therapeutic agent in various diseases (diabetes, CVDs, cancer, cerebral ischemia, neuro and liver damage) and possesses anti-oxidant, antimicrobial, anti-inflammatory, and antiendotoxic activities. Vitexin (apigenin-8-C-glucoside) has also shows the wide range of pharmacological effects, including but not limited to anti-oxidant, anti-cancer, anti-inflammatory, and neuroprotective effects. Vanillic acid shows the anti-cancer activity.